Firm Value Mediates The Influence of Profitability, Firm Size and Sales Growth on Financial Distress - Asmi, Rahmawati; Suryadi, Nanda; Zerrin, Zerrin (Lembaga Riset dan Inovasi Al-Matani, 2024)
This study aims to determine the direct influence of profitability, company size, sales growth on financial distress, in addition to determining the indirect influence of profitability, company size and sales growth on financial distress through company value. This type of research is quantitative with a sample used by 220 companies from a population of 84 food and beverage subsector companies listed on the IDX in 2018-2022. This study uses secondary data published by the Indonesia Stock Exchange. Data analysis was carried out with a quantitative approach using the SmartPLS model version 3.0 The results of this study show that: Profitability has a positive and insignificant effect on Financial distress, profitability affects company value, Company Size does not affect financial distress, company size affects company value, sales growth does not affect financial distress, sales growth does not affect value company, Company value affects financial distress, Company value is unable to mediate the relationship of profitability to financial distress, Company value is unable to mediate the relationship of company size to financial distress, Company value is unable to mediate the relationship of sales growth to financial distress.